Dynamic Compressive and Tensile Characteristics of a New Type of Ultra-High-Molecular Weight Polyethylene (UHMWPE) and Polyvinyl Alcohol (PVA) Fibers Reinforced Concrete - Bashir H. Osman; Xiao Sun; Zhenghong Tian; Hao Lu; Guilin Jiang (Shock and Vibration)
The dynamic mechanical properties of concrete materials are important parameters for evaluating the safety performance of concrete structures under dynamic loads. Fiber cement-based materials have been widely used in the construction projects due to their strength, toughening, and cracking resistance. In this study, we conducted experimental and theoretical studies on dynamic compression and tensile mechanical properties of different proportions of new-type fiber concrete. A Split-Hopkinson pressure bar equipment was used to determine the concrete behavior at different strain rates. The effects of strain rate and fiber content on the strength of the specimen, dynamic increase factor, and ultimate strain were analyzed. Based on the macrodamage factor, the traditional nonlinear viscoelastic constitutive model was simplified and improved. The four-parameter constitutive model was obtained, and the influence of these parameters on the performance of fiber concrete was analyzed. The experimental results were compared with those predicted from the available equations, and results were in accordance. Finally, an analytical equation for predicting the dynamic compression and tensile properties of these new-type fibers was proposed.